Evaluation of the urban Land use plan’s effectiveness in achieving resource efficiency: the case of Bahir Dar city- Ethiopia - Behailu Melesse Digafe; Achamyeleh Gashu Adam; Gebeyehu Belay Shibeshi (International Journal of Urban Sustainable Development, 2024)
Urban land use plans (ULUPs) contribute to the efficient use of resources for sustainable urban development. However, the metered contribution of Bahir Dar’s ULUPs to the efficient use of resources has not yet been known. Bahir Dar is the capital of the Amhara Region and a scenic city on the southern shore of Lake Tana, Ethiopia’s largest lake and the source of the Blue Nile. It attracts many visitors from inside and outside the country. This study evaluates the effectiveness of ULUPs in Bahir Dar to achieve efficient use of resources such as water, energy, and food. Thus, the study developed criteria to assess the effectiveness of ULUPs based on the global indicator framework for the Sustainable Development Goals (SDGs). The results show that its ULUPs were not resource efficient in terms of food production, water quality and yield, and transport energy usage.